Promising Low-cost Adsorbent from Desiccated Coconut Waste for Removal of Congo Red Dye from Aqueous Solution - Abdul Rahim, A.R. (Springer Science and Business Media Deutschland GmbH, 2021)
This study measures and evaluates the capabilities of desiccated coconut waste, a waste by-product produced from coconut milk processing, as an adsorbent precursor for the removal of azo dyes in wastewater. The results show that the desiccated coconut waste performed the highest adsorption capacity towards the Congo Red dye in pH 2 condition where the Qmax = 0.071Â mmol/g. The adsorption capacity of the coconut waste-based adsorbent is relatively high in azo dye removal among the tested waste precursors such as coir pith, tamarind fruit shells, hazelnut shells, and banana peel. The analysis of azo dye adsorption equilibrium and kinetics using appropriate isotherm and kinetic model shows excellent fitting with Langmuir isotherm and pseudo-second-order kinetic model, where the determination coefficient, R2 â 1, indicates a monolayer chemical adsorption process, with a maximum monolayer capacity of 0.004Â mmol/g. These findings support that coconut waste-based adsorbent is highly potential for application of Congo Red removal in wastewater. Â© 2021, The Author(s), under exclusive licence to Springer Nature Switzerland AG.